Ethogram Characteristics of Silver Carp (Hypophthalmichthys molitrix) During the Breeding Period Based on the PAE Coding System - Min Wang; Fengyue Zhu; Lixiong Yu; Qingrui Yang; Ke Wang; Mingdian Liu; Xinbin Duan; Daqing Chen (Animals)
Animal behavior diversity is a key element of biodiversity, and the establishment of an ethogram provides a crucial framework for exploring the relationship between behavioral patterns and environmental factors. However, the development of ethograms and the quantitative analysis of behavioral diversity in fish remain underexplored. In this study, focal animal sampling and instantaneous scan sampling methods, paired with the PAE (Posture-Act-Environment) coding system, were employed to investigate the ethogram and reproductive behavior diversity of silver carp. The findings revealed 12 postures, 20 actions, and 34 behaviors documented during the breeding period of silver carp. Analysis of reproductive behavior diversity revealed that the absolute behavioral diversity index (H), relative behavioral diversity index (r), and regulated diversity index (r-variable) all peaked during the 10–15 h interval following induced spawning. Notably, significant differences (p < 0.001) were observed in these indices across different post-induction time intervals and between sexes. Throughout the breeding cycle, females demonstrated lower diversity and intensity in reproductive behaviors compared to males, suggesting distinct reproductive strategies between the sexes. The reproductive behavior of silver carp exhibited distinct chronobiological disorganization patterns. This study provides a scientific basis for future research on the behavioral ecology of silver carp and the conservation of their wild populations.